2017
DOI: 10.1126/sciimmunol.aal4656
|View full text |Cite
|
Sign up to set email alerts
|

Multicohort analysis reveals baseline transcriptional predictors of influenza vaccination responses

Abstract: Annual influenza vaccinations are currently recommended for all individuals 6 months and older. Antibodies induced by vaccination are an important mechanism of protection against infection. Despite the overall public health success of influenza vaccination, many individuals fail to induce a substantial antibody response. Systems-level immune profiling studies have discerned associations between transcriptional and cell subset signatures with the success of antibody responses. However, existing signatures have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 119 publications
(88 citation statements)
references
References 64 publications
6
77
1
Order By: Relevance
“…We also determined the baseline transcriptome prior to vaccination: previous studies have investigated whether there is a link between baseline gene signatures and immunogenicity. When the gene signature in the current study was compared to a meta-analysis of influenza vaccine studies 15 , we did not see a consistent difference between pregnant and non-pregnant women in genes that were associated with increased expression in high responders to the vaccine. Interestingly, of the genes with reduced expression associated with high responders measured in the current study, PTPN22, PURA, CASP6 and PPIB all had lower levels of expression in pregnancy.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…We also determined the baseline transcriptome prior to vaccination: previous studies have investigated whether there is a link between baseline gene signatures and immunogenicity. When the gene signature in the current study was compared to a meta-analysis of influenza vaccine studies 15 , we did not see a consistent difference between pregnant and non-pregnant women in genes that were associated with increased expression in high responders to the vaccine. Interestingly, of the genes with reduced expression associated with high responders measured in the current study, PTPN22, PURA, CASP6 and PPIB all had lower levels of expression in pregnancy.…”
Section: Discussioncontrasting
confidence: 60%
“…While we did not analyse the immune responses to the vaccines, a recent study has looked at the transcript levels as baseline predictors of immunogenicity 15 . When comparing the expression of the suggested marker genes from the published study in pregnancy, we observed the following: among the genes that were associated with a higher response when upregulated, the genes ARRB1, DPP3 and ACTB were significantly higher expressed in non-pregnant compared to pregnant women; there was no difference in expression for MVP, PLEKHB2 or ARPC4 genes and gene expression for GRB2 and RAB24 was higher in pregnant women.…”
Section: Vaccination Induces a Similar Response In Pregnant And Nonprmentioning
confidence: 99%
“…By computing effect sizes for each data set independently, MetaIntegrator embraces heterogeneity and avoids the limitations of batch effect correction. We have demonstrated application of this framework across a broad spectrum of diseases, including cancer (16,17), solid organ transplant (13), sepsis (18), viral infection (19), tuberculosis (20), neurodegenerative diseases (21), vaccination (22), and SSc (23). Here, we applied the framework to analyze 40 publicly available whole transcriptome profile data sets containing 7471 samples from patients with SLE, individuals with other autoimmune diseases or infections, and healthy volunteers.…”
Section: Introductionmentioning
confidence: 99%
“…Koff is particularly interested in the hypothesis that each person has an innate immune setpoint that may be used to predict the outcome of immunization. [28][29][30][31][32] Finding ways to modulate that setpoint could increase vaccine efficacy.…”
Section: A Possible New Paradigm For Vaccine Trialsmentioning
confidence: 99%